COMPARATIVE EGG PRODUCTION OF MYLABRIS PUSTULATA THUNB. (COLEOPTERA : MELOIDAE) ON FLOWER BUDS OF CONVOLVULACEOUS HOSTS - KRISHNAN, N.; DINAKARAN, S.; JEYAKUMAR, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Impacts of flower buds of two convolvulaceous food plants (Ipomoea cornea and Ipomoea tuberosa) on egg production by Mylabrispustulata Thunbis investigated. Maximum egg production is noticed in females fedon flowers and buds of I. corneathan those fedon I tuberosa. Egg production is significantly declined in females fed on the flowerbuds of both host plants.